High-Level Congruence of Myrionecta rubra Prey and Dinophysis Species Plastid Identities as Revealed by Genetic Analyses of Isolates from Japanese Coastal Waters - Nishitani, Goh (American Society for Microbiology (ASM), 2010)
We analyzed cryptophyte nucleomorph 18S rRNA gene sequences retained in natural Myrionecta rubra cells and plastid 16S rRNA gene and psbA sequences retained in natural cells of several Dinophysis species collected from Japanese coastal waters. A total of 715 nucleomorph sequences obtained from 134 M. rubra cells and 564 plastid 16S rRNA gene and 355 psbA sequences from 71 Dinophysis cells were determined. Almost all sequences in M. rubra and Dinophysis spp. were identical to those of Teleaulax amphioxeia, suggesting that M. rubra in Japanese coastal waters preferentially ingest T. amphioxeia. The remaining sequences were closely related to those of Geminigera cryophila and Teleaulax acuta. Interestingly, 37 plastid 16S rRNA gene sequences, which were different from T. amphioxeia and amplified from Dinophysis acuminata and Dinophysis norvegica cells, were identical to the sequence of a D. acuminata cell found in the Greenland Sea, suggesting that a widely distributed and unknown cryptophyte species is also preyed upon by M. rubra and subsequently sequestered by Dinophysis. To confirm the reliability of molecular identification of the cryptophyte Teleaulax species detected from M. rubra and Dinophysis cells, the nucleomorph and plastid genes of Teleaulax species isolated from seawaters were also analyzed. Of 19 isolates, 16 and 3 clonal strains were identified as T. amphioxeia and T. acuta, respectively, and no sequence variation was confirmed within species. T. amphioxeia is probably the primary source of prey for M. rubra in Japanese coastal waters. An unknown cryptophyte may serve as an additional source, depending on localities and seasons.